Pengaruh Pelatihan Kerja, Budaya Organisasi, Pengembangan Karir dan Kompetensi Terhadap Kepuasan Kerja Pegawai Pada Dinas Tenaga Kerja Dan Mobilitas Penduduk Aceh - Nuzulman, Nuzulman Nuzulman; Safitri, Husnaina Mailisa; Budi, Arief Setia; Nabila, Siti Salwa (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
The research was carried out because the researcher found indications of low level of employment satisfaction among the staff, an organizational culture in the service that is not fully conducive, unclear and limited career development paths and a fairly low degree of staff competence. The aim of the study is to test and analyze the impact of employment education, organization culture, careers and competences on employment satisfaction of employees on the workforce and mobility of the population. As for the research method used, it is a quantitative type associative method with a dual linear regression model. The research results show that the job training variable has a partial effect on job satisfaction, while organizational culture, career development and competence have no effect. Meanwhile, simultaneously the variables of job training, organizational culture, career development and competence influence job satisfaction. Keywords : Job Training, Organizational Culture, Career Development, Competency, and Job Satisfaction